Per- and polyfluoroalkyl (PFASs) contamination profiles in water and sediments for two contrasting lakes in southern and northern Sweden - Mussabek, Dauren; Berndtsson, Ronny ; 0000-0003-1473-0138; Persson, Kenneth M; Ahrens, Lutz; Jakobsson, Kristina (SETAC Europe 26th Annual Meeting, Nantes, France, 2016-05-22 - 2016-05-26, 2016)
Perfluoroalkyl and polyfluoroalkyl substances (PFASs) are becoming an increasingly global concern. PFASs are highly fluorinated organic chemicals that represent a serious risk for environmental and human health. Due to their toxicological impact, PFASs are now included in several emission regulations. Even if the global level of PFASs use is decreasing much of present concentrations in the environment are results of usage and exposure in the past. Therefore, observation of current environmental concentrations and transport patterns may lead to better prediction of their potential environmental distribution, health impact, and future fate. Investigation of PFASs distribution profiles was carried out in surface waters and sediments of the two lakes Sänksjön and Langsjön in southeast and northeast of Sweden. In total 11 sediment cores and 6 water samples were collected to investigate the PFASs concentration by using high-performance liquid chromatograph-tandem mass spectrometer (HPLC-MS/MS). The concentration of PFASs in sediment ranged from 2.7 to 216 ng g-1 dry weight for the Sänksjön lake and from 0.8 to 78 ng g-1 dry weight for the Langsjön lake. The PFAS concentrations and distribution were correlated to investigate transport conditions for different PFASs and to determine the possible exposure time sequence for each sampling site. Selected water and sediment properties such as pH, conductivity, and total organic carbon were correlated to observed PFAS concentrations. The results for water samples reflect the high contamination of surface water in both lakes. The maximum concentrations were 79 and 1885 ng L-1 for Sänksjön and Langsjön, respectively. Analysis of sediment cores reflects the temporal evolution of discharge patterns to the two lakes. The correlation of selected samples suggests transport and degradation mechanisms.